Role of K-feldspar dissolution in chloritization of smectite: Insights from hydrothermal experiments - Anas Muhammad Salisu; Abdulwahab Muhammad Bello; Abduljamiu O. Amao; Khalid Al-Ramadan (Applied Clay Science, 2026)

Climate change reshapes plant–microbe–pest interactions and accelerates the need for advanced crop protection strategies - Muhammad Anas; Vildan Altun; Waseem Ahmed Khattak; Sameel Hassan; Erdogan E. Hakki (Physiological and Molecular Plant Pathology, 2026)

Physiological and molecular mechanisms underlying crop responses to pest attack and their implications for sustainable management - Waseem Ahmed Khattak; Minhas Elahi; Muhammad Anas; Fatima Ijaz; Sania Noor; Javed Iqbal (Physiological and Molecular Plant Pathology, 2026)

Phosphatidylethanolamine-mediated metabolic membrane remodeling in obesity-associated Alzheimer’s disease: mechanisms, neuroimmune crosstalk, and therapeutic potential - Mumtaz Ahmad; Moh Aijaz; Mohamamd Anas Ansari; Muhammad Afzal (Metabolic Brain Disease, 2026)

Nanoclay-phosphate Fertilizers for Calcareous Soils: Mechanistic Insights, Computational Design, and Agronomic Implications - Muhammad Anas; Malica Younas; Sani Isnain; Waseem Ahmed Khattak; Minhas Elahi; Münüre Tanur Erkoyuncu; Erdogan E Hakki (Journal of Soil Science and Plant Nutrition, 2026)

Melatonin and melatonin-functionalized quantum dots enhance antioxidant defense, attenuate cadmium uptake, and improve yield performance in bread wheat under cadmium stress - Shiza Mukhtar; Samina Bibi; Muhammad Anas; Munaza Mehreen; Umar Masood Quraishi (Biocatalysis and Agricultural Biotechnology, 2026)

Salicylic Acid and Proline-Functionalized Carbon Quantum Dots Mitigate Nickel Toxicity in Wheat by Enhancing Antioxidant Defense, Metal Homeostasis, and Nutritional Quality - Syed Abu Bakr Haider Bukhari; Minhas Elahi; Muhammad Anas; Shoaib Abbas; Waseem Ahmed Khattak; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2026)

Artificial intelligence for physiological and molecular monitoring, detection, and forecasting of potato late blight - Sani Isnain; Muhammad Anas; Anees Ali; Sezai Erci̇şli̇ (Physiological and Molecular Plant Pathology, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

A new ecological index for assessing benthic invertebrate assemblages in tropical coral reef ecosystems - Hadiyanto Hadiyanto; Indra Bayu Vimono; Hendrik Alexander William Cappenberg; Ludi Parwadani Aji; Teddy Triandiza; Ana Setyastuti; Ismiliana Wirawati; Ernawati Widyastuti; Rianta Pratiwi; Putri Saphira Ibrahim; Tyani Fitrian; Allsay Kitsash Addifisyukha Cintra; et al. (Aquatic Sciences, 2026)

“Ondansetron augmentation for obsessive–compulsive disorder: A systematic review and meta-analysis of randomized placebo-controlled trials” - Anas Mohammad; Mohammad Ibrahim; Aneeq Mahmood Khan; Usama Pervaiz; Sarah Aijaz; Muhammad Hassnain Nasrullah; Hammad Jamil (European Journal of Clinical Pharmacology, 2026)

Comparative analysis of machine learning and neural network models for petrophysical property prediction in heterogeneous reservoirs - Zayan Khursheed; Muhammad Anas Jawaid; Muhammad Mustafa; Shaine Mohammadali Lalji; Syed Imran Ali; Mohsin Ayubi (Next Research, 2026)

Experimental and predictive advancements in hydrogen enriched compressed natural gas spark ignition engines: a critical review - Muhammad Farhan; Hamza Ahmad Salam; Muhammad Ihsan Shahid; Tianhao Chen; Qiuhong Xiao; Long Jiang; Anas Rao; Xin Li; Fanhua Ma (Fuel, 2026)

Mitigating Chromium-Induced Toxicity in Wheat Using Quantum Dots: Physiological, Biochemical, and Seed Composition Responses in SKD-1 and Borlaug-16 Cultivars - Muhammad Anas; Amjid Khan; Umar Masood Quraishi (Journal of Soil Science and Plant Nutrition, 2026)

Single and Multi-Strain PGPR Enhance Salinity Tolerance in Canola (Brassica napus L.) Seedlings - Münüre Tanur Erkoyuncu; Muhammad Anas; Erdogan Esref Hakki (Journal of Soil Science and Plant Nutrition, 2026)
Salinity is a major abiotic stress limiting canola ( Brassica napus L.) productivity, especially in arid regions. This study aimed to evaluate the efficiency of plant growth-promoting rhizobacteria (PGPR) in enhancing early seedling tolerance to graded sodium chloride (NaCl) stress and to compare single- and multi-strain inoculations. A greenhouse experiment was conducted under NaCl concentrations ranging from 0 to 200 mM using three treatments: uninoculated control, single strain ( Bacillus subtilis , SB), and a triple-strain consortium ( Bacillus megaterium + Pseudomonas fluorescens + B. subtilis , TB). Growth, physiological, and biochemical traits were analysed, including relative water content (RWC), electrolyte leakage (EC), photosynthetic pigments, phenolic compounds, oxidative stress markers, and antioxidant enzyme activities such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX). Salinity significantly reduced relative water content (RWC) from 60.10% to 48.63% and increased electrolyte leakage (EC) from 62.79% to 77.95%. TB inoculation mitigated these effects by maintaining higher RWC (53.57%) and lower EC (66.40%) than the control (71.93%). TB-treated plants showed higher chlorophyll (0.84 mg g⁻¹ FW), phenolics (10.34 mg GAE g⁻¹ DW ) , flavonoids (4.10 mg QE g⁻¹ DW ) , antioxidant capacity (85.98%), and proline (122.36 mg g⁻¹ FW ) compared to controls. Oxidative damage decreased, with hydrogen peroxide (H₂O₂) and malondialdehyde (MDA) reduced to 14.01 µmol g⁻¹ FW and 60.22 nmol g⁻¹ FW, respectively. Enzymatic responses differed: SB enhanced SOD and CAT under moderate salinity, while TB increased POD and APX activities under mild stress. PGPR inoculation, particularly multi-strain consortia, alleviates salt-induced oxidative stress and improves osmotic adjustment and antioxidant defense in canola seedlings, offering an eco-friendly strategy for sustainable production in saline soils. Graphical Abstract

Is Critical Period for Weed Control Influenced by the Application of Pre-emergence Herbicide in Lentil (Lens culinaris Medik.)? - Muhammad Zia Ul Haq; Anas Ali; Gul Zaib Hassan; Rana Nadeem Abbas; Saira Shafiq; Mubashar Nadeem (International Journal of Plant Production, 2026)

The potential of natural deep eutectic solvent in polyphenol extraction of Timonius flavescens (Jacq) Baker as an anti-breast cancer agent and its toxicity evaluation - Muhammad Fauzan Lubis; Retno Murwanti; Poppy Anjelisa Zaitun Hasibuan; Sumaiyah Sumaiyah; Nur Aira Juwita; Ana Yulyana; Ririn Astyka; Sri Yuliasmi; Lokot Donna Lubis; Wardiyah Daulay; Khairani Fitri (Advances in Traditional Medicine, 2026)

Efficacy of chimeric antigen receptor natural killer cells in treatment of ovarian cancer. A meta-analysis of pre-clinical studies - Nabeel Ahmed; Jawaria Jabeen; Malja Rehman; Safa Noor; Sana Tahseen; Asmaa Qamar; Muhammad Anas; Muhammad Muneeb Khalid; Taseer Ahmad; Weiqun Wang; Lechun Lyu (Immunologic Research, 2026)

Adaptive Strategies of Carpet Grass to Drought: Insights from Physiological and Antioxidant Responses - Mohsin Nawaz; Samina Shabbir; Muhammad Mudassir Nazir; Muhammad Anas; Muhammed Farooq; Hu Xu; Wu Yang; Parvaiz Ahmad; Liao Li; Zhiyong Wang (Journal of Plant Growth Regulation, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Environmental geochemistry of emerging contaminants: impacts on agroecosystem function, food security, and human health - Muhammad Anas; Vildan Altun; Waseem Ahmed Khattak; Amjid Khan; Sezai ERCİŞLİ; Khalid Ali Khan; Erdogan E. Hakki (Environmental Geochemistry and Health, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

Performance assessment of a vibrating-fin atmospheric water generator under variable weather conditions in North Africa's arid mediterranean climate - Muhammad I. Rashad; Anas M. Shishiny; Maya O. Mostafa; Youssef Mohab; Shehab Ahmed; Mohamed A. Farahat (Journal of Water Process Engineering, 2026)

Corrigendum to “Spatio- temporal juvenile corals (Scleractinia) following the 2016 coral bleaching event at the Pieh Islands Marine Tourism Park (PIMTP), West Sumatra Province, Indonesia” [Reg. Stud. Mar. Sci. 75 (2024) 103533] - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Risandi Dwirama Putra; Ni Wayan Purnama Sari; Rikoh M. Siringoringo; Tri Aryono Hadi; Giyanto; Raden Sutiadi; Ana Faricha; Yuwanda Ilham; et al. (Regional Studies in Marine Science, 2025)

Genome-wide identification and transcriptome-based expression analysis of hybrid sugarcane calmodulin-binding transcription activators under drought - Vitor Luciano Costa da Silva; Ana Maria Martinez; Maqsood Alam; Muhammad Noman; Antonio Chalfun-Junior (Plant Gene, 2025)

Analysis of exhaust heat recovery and hydrogen production by steam methane reforming under different operating conditions of the HCNG engine - Muhammad Ihsan Shahid; Muhammad Farhan; Anas Rao; Muhammad Saddam Hussain; Xianlei Zhu; Hamza Ahmad Salam; Tianhao Chen; Xin Li; Fanhua Ma (Fuel, 2025)

Correction: Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

Rosa moschata leaf extract modulates complete freund’s adjuvant-induced polyarthritis in Wistar rats via regulation of pro-inflammatory and inflammatory biomarkers - Amr S. Abouzied; Uzma Saleem; Maryam Farrukh; Umme Farwa; Areej M. Alsolami; Fatima A. Jaber; Tourki A. S. Baokbah; Ibrahim Aljaezi; Nouf Abdullah Alharbi; Muhammad Ajmal Shah; Ana Sanchez Silva; Norah K. Algarzae (Inflammopharmacology, 2025)

Ethnobotanical inventory and threat assessment of medicinal plants in Lajbouk Valley, Khyber Pakhtunkhwa, Pakistan - Shaha Buddin; Syed Mukaram Shah; Muhammad Ibrahim; Mohsin Ullah; Waseem Ahmed Khattak; Muhammad Anas; Asif Kamal (Genetic Resources and Crop Evolution, 2025)

Exploring ethnoveterinary practices: a comprehensive study of medicinal plants in Bannu District, Khyber Pakhtunkhwa, Pakistan - Waseem Ahmed Khattak; Malka Saba; Minhas Elahi; Muhammad Anas; Qurban Ali Magsi; Rabia Tabassum; Adnan Khattak; Muhammad Majeed; Murad Muhammad (Genetic Resources and Crop Evolution, 2025)

Predicting microplastic accumulation zones and shoreline changes along the Kelantan coast, Malaysia, using integrated GIS and ANN models - Muhammad Zakwan Anas Abd Wahid; Anis Syuhada Saufi; Nurul Aliah Farhana Kamarulzaman; Mohamed Syazwan Osman; Mohamad Sufian So'aib; Samsul Setumin; Adi Izhar Che Ani; Fathinul Najib Ahmad Saad (Marine Pollution Bulletin, 2025)

Response of invasive Solidago canadensis to foliar application of natural herbicide and glyphosate - Muhammad Anas; Zhi-Yun Huang; HuAnHe Xiong; Muhammad Imran; Meng-Ting Yan; Qaiser Javed; Guang-Qian Ren; Shan-Shan Qi; Jian Li; Zhi-Cong Dai; Dao-Lin Du (Journal of Environmental Management, 2025)

Alien flora of the Kingdom of Saudi Arabia: taxonomic composition, phylogenetic patterns, and invasion status - Shiekh Marifatul Haq; Muhammad Waheed; Muhammad Azhar Jameel; Łukasz Walas; M. Nasir Khan; Manzer H. Siddiqui; Saud Alamri; Anas E. AbuYahya; Rainer W. Bussmann (Biological Invasions, 2025)

Thriving amidst adversity: Responses of karst vegetation to extreme compound droughts - Linying Xiao; Xiuqin Wu; Changqing Guo; Zichun Lu; Muhammad Anas Khan; Chenghao Zheng; Jinxing Zhou (Journal of Hydrology, 2025)

Corrigendum to: “Substitution of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China” [J Hazard Mater 465 (2024) 1–14 133118] - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2025)

Non-linear complementarity model including large displacements and strain rate effects for RC beams under impact - Muhammad Anas; Haseeb Ahmed; Azam Khan; Mudassir Arshad; Moiz Tariq (Engineering Structures, 2025)

Correction: Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Advancing energy-related climate mitigation technologies in arctic region: the impact of green finance and critical mineral resources - Muhammad Anas; Wei Zhang; Talal H. Alsabhan; Liaqat Ali; Jie Han (Climatic Change, 2025)

The Role of Silver Nanoparticles and Bacillus subtilis in Modulating Morpho–Physio–Biochemical Responses in Wheat (Triticum aestivum L.) Under Arsenic Stress - Mohammad K. Okla; Sadia Javed; Muhammad Faran Tahir; Ibrahim A. Saleh; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Abdulrahman Abdullah Alatar; Bandar M. AlMunqedhi; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)
Soil contamination with toxic heavy metals [such as arsenic (As)] is becoming a serious global problem because of the rapid development of the social economy. Although plant growth-promoting rhizo-bacteria (PGPR) and nanoparticles (NPs) are the major protectants to alleviate metal toxicity, the study of these chemicals in combination to ameliorate the toxic effects of As is limited. Therefore, the present study was conducted to investigate the effects of different levels of Bacillus subtilis (5 and 10 mg L –1 ) and silver (Ag)–NPs (10 and 20 mg kg –1 ) on morpho-physiological and antioxidative defense attributes, which was spiked with different levels of As [0 mM (i.e., no As), 100, and 200 mg kg –1 ] in wheat ( Triticum aestivum L.) seedlings. Results from the present study showed that the increasing levels of As in the soil significantly ( P < 0.05) decreased plant growth and biomass, photosynthetic pigments, gas exchange attributes, sugars, and nutritional contents from the roots and shoots of the plants. In contrast, increasing levels of As in the soil significantly ( P < 0.05) increased oxidative stress indicators in term of malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and electrolyte leakage (EL), and also increased organic acid exudation patter in the roots of T. aestivum . The negative impact of As toxicity can overcome the application of B . subtilis and Ag − NPs, which ultimately increased plant growth and biomass by capturing the reactive oxygen species (ROS), and decreased oxidative stress in T. aestivum by decreasing the As contents in the roots and shoots of the plants. Research findings, therefore, suggest that the combined application of B . subtilis and Ag − NPs can ameliorate As toxicity in T. aestivum , resulting in improved plant growth and composition under metal stress, as depicted by balanced exudation of organic acids. Graphical Abstract

Enhancing accuracy in flexural strength prediction of glass fibre-reinforced concrete via TPE-XGB algorithm and explainable machine learning - Muhammad Abdullah Khan; Anas Rahat Ullah; Danish Mukhtiar; Muhammad Shahid Siddique; Muhammad Hammad Iqbal; Waleed Bin Inqiad (Innovative Infrastructure Solutions, 2025)
This study aims to accurately predict the flexural strength (FS) of glass fiber reinforced concrete (GFRC) using advanced machine learning (ML) techniques. A novel algorithm, tree structured parzen estimator based extreme gradient boosting (TPE-XGB), is proposed by integrating Bayesian optimization (TPE) for automated hyperparameter tuning with the predictive strength of XGB. In addition to TPE-XGB, other ML algorithms including bagging regressor (BR), gene expression programming (GEP), and multi expression programming (MEP) are also employed for comparison. A comprehensive dataset consisting of 227 experimental instances of GFRC flexural strength was compiled from 33 internationally published studies. The models were trained and evaluated using statistical error metrics, k fold cross validation, scatter plots, and residual analysis. Results showed that all models performed reliably, with TPE-XGB achieving the highest prediction accuracy (testing R 2 value of 0.972). In contrast, GEP and MEP, described as grey box models that produce interpretable mathematical expressions, offered empirical equations for FS prediction which enhanced transparency. To further address the non-transparent nature of black box models like TPE-XGB, explainable machine learning (XML) techniques were applied. These included SHAP (Shapley Additive Explanations), Individual Conditional Expectation (ICE), and Partial Dependence Plots (PDP). The analysis revealed that water to cement ratio, quantities of fine and coarse aggregates, and glass fiber content were the most influential variables affecting the flexural performance of GFRC. Finally, a graphical interface is proposed to demonstrate the practical usability of the developed models. This study contributes both accurate prediction tools and interpretable insights, supporting improved and informed design practices in concrete technology.

Dense vegetation as a natural buffer: Mitigating and decelerating drought propagation - Linying Xiao; Changqing Guo; Chenghao Zheng; Zichun Lu; Muhammad Anas Khan; Jinxing Zhou; Xiuqin Wu (Journal of Environmental Management, 2025)

Bioremediation of petroleum contaminated water using oil spill dispersant and Lemna minor in laboratory-scale constructed wetland - Muhammad Ridho Fitrisyah; Anas Miftah Fauzi; Mohamad Yani (Wetlands Ecology and Management, 2025)

Finding the Best Growth Media for Kiwifruit Cv. ‘Hayward’ Seedling Rootstocks in Mansehra District, Pakistan - Sadaf Bibi; Aftab Afzal; Ghulam Mujtaba Shah; Abdul Waheed; Muhammad Anas; Waseem Ahmed Khattak; Shah Fahad (Applied Fruit Science, 2025)

Individual and combinatorial application of indole−3−acetic acid and salicylic acid in barley (Hordeum vulgare L.): Assessing morpho−physio−biochemical responses under copper stress - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Suliman Mohammed Suliman Alghanem; Muhammad Faran Tahir; Muhammad Anas; Muhammad Hamzah Saleem; Hosam O Elansary; Eman A. Mahmoud (South African Journal of Botany, 2025)

Rapid wall shear stress prediction for aortic aneurysms using deep learning: a fast alternative to CFD - Md. Ahasan Atick Faisal; Onur Mutlu; Sakib Mahmud; Anas Tahir; Muhammad E. H. Chowdhury; Faycal Bensaali; Abdulrahman Alnabti; Mehmet Metin Yavuz; Ayman El-Menyar; Hassan Al-Thani; Huseyin Cagatay Yalcin (Medical & Biological Engineering & Computing, 2025)
Aortic aneurysms pose a significant risk of rupture. Previous research has shown that areas exposed to low wall shear stress (WSS) are more prone to rupture. Therefore, precise WSS determination on the aneurysm is crucial for rupture risk assessment. Computational fluid dynamics (CFD) is a powerful approach for WSS calculations, but they are computationally intensive, hindering time-sensitive clinical decision-making. In this study, we propose a deep learning (DL) surrogate, MultiViewUNet, to rapidly predict time-averaged WSS (TAWSS) distributions on abdominal aortic aneurysms (AAA). Our novel approach employs a domain transformation technique to translate complex aortic geometries into representations compatible with state-of-the-art neural networks. MultiViewUNet was trained on $$\varvec{23}$$ 23 real and $$\varvec{230}$$ 230 synthetic AAA geometries, demonstrating an average normalized mean absolute error (NMAE) of just $$\varvec{0.362%}$$ 0.362 % in WSS prediction. This framework has the potential to streamline hemodynamic analysis in AAA and other clinical scenarios where fast and accurate stress quantification is essential. Graphical abstract

Omics Technologies: Unraveling Abiotic Stress Tolerance Mechanisms for Sustainable Crop Improvement - Muhammad Hamzah Saleem; Sana Noreen; Izwa Ishaq; Ammara Saleem; Khalid Ali Khan; Sezai Ercisli; Muhammad Anas; Awais Khalid; Temoor Ahmed; Ammara Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Protease activated receptor inhibitors in rheumatoid arthritis: a new frontier in treatment - Tayyaba Rana; Huma Hameed; Ana Cláudia Paiva-Santos; Muhammad Jamshaid; Muneeba Anwar (Inflammopharmacology, 2025)

Green-fabricated MnO₂ nanoparticles function as dual nanofertilizers and chromium remediators, enhancing antioxidant pathways, ionomic networks, and physiological resilience in wheat - Muhammad Anas; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Restoring wheat productivity and nutrient balance under cadmium stress through reducing toxicity, metal uptake, and oxidative damage using selenium nanoparticles - Ayesha Jamil Abbasi; Muhammad Anas; Minhas Elahi; Amjid Khan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Shah Fahad; Hosam O. Elansary; Eman A. Mahmoud; Temoor Ahmed; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Individual and Combinatorial Applications of Arbuscular Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Increase Morpho-Physio-Biochemical Responses in Rice (Oryza sativa L.) under Cadmium Stress - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Sadia Javed; Muhammad Faran Tahir; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Mohammed O. Alshaharni; Eman Fayad; Khalid Ali Khan; Awais Khalid; Shafaqat Ali; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Assessing the impact of risk perception on fisheries performance: a structural equation modeling approach in coastal fisheries - Muhammad Mohsin; Hengbin Yin; Ana Mehak (Frontiers in Marine Science, 2025)
Risk perception is crucial for making effective fisheries management strategies. However, this role of risk perception needs to be addressed, particularly in developing countries. Published literature documents such a scenario in the case of Pakistan, which results in a decreased economic contribution to the fisheries sector. Despite its importance, the role of risk perception in managing the fisheries sector is absent in online scientific studies. The present study strives to address this research void by analyzing survey-based data collected through snowball sampling between May 2022 and October 2024. Multivariate analysis, viz., Structure Equation Modeling (SEM), was done through Statistical Package for Social Sciences (SPSS) as well as Analysis of Moment Structures (AMOS). Cronbach’s alpha values for all constructs were above 0.6, with the highest being 0.962 for policies and regulations risk, confirming data reliability. Confirmatory Factor Analysis (CFA) indices, including Comparative Fit Index (CFI) (0.933) and Tucker-Lewis index (TLI) (0.916), indicated a good model fit, with acceptable construct reliability (CR) and Average Variance Extracted (AVE) values. SEM showed that economic risk (estimate = -0.425, p = 0.000), environmental risk (estimate = -0.251, p = 0.007), and consumption risk (estimate = -0.265, p = 0.000) negatively impacted performance, while policies and regulations risk (estimate = -0.113, p = 0.121) and infrastructure and logistics risk (estimate = -0.073, p = 0.411) were insignificant. Risk perception was a significant mediator of performance, with varying effects across Sindh and Balochistan. According to the survey participants, there is a dire need to increase levels of fisheries risk perception, which can be achieved through properly designed capacity-building and incentive-based management techniques. Furthermore, this study discusses the practical implications and limitations.

Exploring FTAs, seafood exports, and SDGs: a gravity model analysis of Pakistan’s seafood trade with China and regional partners - Yuxiang Xia; Hengbin Yin; Muhammad Mohsin; Ana Mehak; Cai Yan (Frontiers in Marine Science, 2025)
This study examines the effects of Free Trade Agreements (FTAs) on Pakistan’s seafood exports, specifically analyzing the China-Pakistan Free Trade Agreement (CP-FTA) and its stages, CP-FTAI and CP-FTAII. Using the gravity model (GM) of trade, it empirically analyzes the dynamics of seafood trade between Pakistan and its neighboring countries, aiming to provide insights into improving trade balance and export performance. The study employs three econometric approaches—Ordinary Least Squares (OLS), Fixed Effects Model (FEM), and Pseudo Poisson Maximum Likelihood (PPML) to ensure the robustness and reliability of the findings. The results reveal that Pakistan’s seafood exports are significantly influenced by FTAs, particularly with Afghanistan, Sri Lanka, and Malaysia, while CPFTA-I shows a positive impact. However, CPFTA-II exhibit negative and insignificant relationship, indicating that external shocks, like the COVID-19 pandemic, have impacted trade dynamics. The results of this study are significantly relevant to multiple United Nations Sustainable Development Goals (SDGs). Notably, they contribute to SDG 8, which focuses on Decent Work and Economic Growth, by promoting trade-driven economic advancement. Furthermore, they support SDG 9, which pertains to Industry, Innovation, and Infrastructure, by facilitating infrastructure development through the China-Pakistan Economic Corridor (CPEC). Additionally, they align with SDG 12, which emphasizes Responsible Consumption and Production by advocating sustainable trade practices. The study recommends enhancing FTAs, improving infrastructure, and expanding trade with neighboring markets to optimize Pakistan’s seafood export potential. Policymakers should focus on strengthening trade agreements, streamlining logistics, and integrating variables like security and exchange rates to develop more resilient and sustainable trade strategies, contributing to important SDGs.

Efficacy of ascorbic acid coated quantum dots in alleviating lead-induced oxidative damage and enhancing growth parameters in rice (Oryza sativa L.) for sustainable cultivation - Aliza Falak; Muhammad Anas; Amjid Khan; Alvina Hayat; Zeenat Shaheen; Muhammad Hamzah Saleem; Shah Fahad; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Enhancing Efavirenz Bioavailability Via Polymer-Based Buccal Administration: Optimization and Characterization of Nanocrystal-Loaded Dissolving Microneedle Delivery Systems - Khairiyah Khairiyah; Muh. Bisfain Asaf; Nur Afni Annisa Achmad; Rachmatya W. Tuna; Irfan Kurniawan; Anugerah Yaumil Ramadhani Aziz; Maria Mir; Juan Domínguez-Robles; Mónica Millán-Jiménez; Ilyas Essadki-Aittaji; Ana B. Cobo-González; Muhammad Aswad; et al. (The AAPS Journal, 2025)

Policy impacts of intellectual property and academic research trends in marine-derived collagen and chitin/chitosan value chains - Helena Vieira; Mariana Almeida; Muhammad Noman Shafique; Miguel C. Leal; Ana I. Lillebø (Marine Policy, 2025)

Energy balance modelling of snow and ice melt for the Naltar catchment (Karakoram, Pakistan) in future climate - Muhammad Usman Liaqat; Ana Casanueva; Rubina Ansari; Giovanna Grossi; Roberto Ranzi (Journal of Hydrology, 2025)

Changes in the probability of temporally compound wet and dry events in a warmer world: case study in the Upper Jhelum Basin—South Asia - Rubina Ansari; Ana Casanueva; Muhammad Usman Liaqat; Giovanna Grossi (Regional Environmental Change, 2025)
Temporal compound events (TCEs), such as the consecutive occurrence of two complementary extremes of the hydrological spectrum (floods and droughts), exhibit a volatile hydrological cycle that exacerbate the challenges associated with water resources management. This study makes use of bias-corrected climate models output from three modeling experiments (CMIP6, CORDEX, and CORDEX-CORE), to examine moderate to extreme wet and dry events and their temporal compounding over the Upper Jhelum Basin (UJB), under low, medium, and high emission scenarios for two future periods (2040–2059 and 2080–2099). Standardized Precipitation Evapotranspiration Index (SPEI) is used to quantify the meteorological wet and dry events that are the main driver of the hydrologic floods and droughts. The two types of TCEs considered in the current study are wet-to-dry (W-to-D) events and dry-to-wet (D-to-W) events in the adjacent month. Results indicate that (1) under warming conditions, wet and dry events are expected to become more frequent and severe whereas duration of the events exhibits distinct change signals depending on the specific location. (2) The basin is more prone to D-to-W TCEs dominated in the southwest of the region, which was not found to be hotspot historically neither for dry nor for wet extreme events. (3) CORDEX and CORDEX-CORE ensembles show varying climate change signals with no specific spatial pattern whereas the CMIP6 ensemble shows stronger change signals and divides the region into two distinct parts, i.e., northeast and southwest.

Combating Mercury Stress in Spinach (Spinacia oleracea L.) with Zinc Oxide and Providencia Vermicola, Assessing Changes in Defense Mechanism and Organic Acid Exudation Patterns - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Sadia Javed; Muhammad Anas; Muhammad Hamzah Saleem; Awais Khalid; Khalid Ali Khan; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

Microbial Interactions and Bacterial Responses to Metal Stress in Plants: Mechanisms, Adaptations, and Applications for Sustainable Agriculture - Muhammad Anas; Aliza Falak; Sameel Hassan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Khalid Ali Khan; Awais Khalid; Shah Fahad (Journal of Crop Health, 2025)

Symbiotic Synergy: Unveiling Plant-Microbe Interactions in Stress Adaptation - Muhammad Anas; Awais Khalid; Muhammad Hamzah Saleem; Khalid Ali Khan; Waseem Ahmed Khattak; Shah Fahad (Journal of Crop Health, 2025)

Application of fertilizers improves cadmium phytoextraction efficiency of Nasturtium officinale R.Br. grown in cadmium-contaminated water - Amjad Ali; Niaz Ali; Yansheng Gu; Nisar Ahmad; Nasar Ali; Israr Ahmad; Ajab Khan; Muhammad Anas; Hamad Ur Rehman; Asmat Ali; Muhammad Inayat Ullah khan (Environmental Monitoring and Assessment, 2025)

Depositional and diagenetic controls on the reservoir quality of marginal marine sandstones: An example from the Early Devonian subbat member, jauf formation, northwest Saudi Arabia - Anas Muhammad Salisu; Hasan Algheryafi; Abdulwahab Muhammad Bello; Abduljamiu O. Amao; Bandar Al-Otaibi; Khalid Al-Ramadan (Marine and Petroleum Geology, 2024)

Adaptive mechanisms of wheat cultivars to lead toxicity through enhanced oxidative defense, ionomic redistribution, and anatomical modifications - Muhammad Anas; Muhammad Saad Bashir; Khadija Saleem; Atika Noor; Umar Masood Quraishi (Journal of Plant Physiology, 2024)

Sustainable Development Goals (SDGs): The nexus of fintech and water productivity in 11 BRICS countries - Cem Işık; Jie Han; Wei Zhang; Anas Muhammad; Stefania Pinzon; Gul Jabeen (Journal of Environmental Management, 2024)

Hydrogen production techniques and use of hydrogen in internal combustion engine: A comprehensive review - Muhammad Ihsan Shahid; Anas Rao; Muhammad Farhan; Yongzheng Liu; Hamza Ahmad Salam; Tianhao Chen; Fanhua Ma (Fuel, 2024)

2D Ti3C2Tx-MXene and its superstructures as dual-function electrodes for triboelectric nanogenerators for self-powered electronics - Shoaib Anwer; Muhammad Umair Khan; Anas Alazzam; Baker Mohammad; Eiyad Abu Nada (Chemical Engineering Journal, 2024)

Cobalt Ferrite@Barium titanate core-shell nanoparticles empowered triboelectric electromagnetic coupled nanogenerator for self-powered electronics - Fandi Jean; Muhammad Umair Khan; Shoaib Anwer; Anas Alazzam; Baker Mohammad (Chemical Engineering Journal, 2024)

Nutritional composition assessment and antimicrobial activity of Catostylus perezi , jellyfish blooms along the coast of Pakistan: an awareness to avoid food neophobia in Pakistan - Muhammad Naveed; Malik Wajid Hussain Chan; Sadar Aslam; Fenghuan Wang; Anas Sajjad; Asad Ullah; Nida Saleem; Muhammad Samee Haider; Victoria Arija (Natural Product Research, 2024)

New insight into the diversity, biometric distribution, and relationships of commercial sea cucumber species from Indonesia - Ana Setyastuti; Ismiliana Wirawati; Hadiyanto Hadiyanto; Nurjamin Nurjamin; Sandi Permadi; Tri Aryono Hadi; Bayu Prayudha; Muhammad Hafizt; Indra Bayu Vimono; Marindah Yulia Iswari; Ludi Parwadani Aji; Ardi Ardiansyah; et al. (Fisheries Research, 2024)

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

Comprehensive insights on treatment modalities with conventional and herbal drugs for the treatment of duodenal ulcers - Huma Hameed; Jahangir Hussain; Ana Cláudia Paiva-Santos; Muhammad Zaman; Ali Hamza; Irsa Sajjad; Faria Asad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Exploring the impact of sustainable finance on carbon emissions: Policy implications and interactions with low-carbon energy transition from China - Wei Zhang; Jie Han; Shiyi Kuang; Cem Işık; Ya Su; Gu Li Ni Ga Er Ju Lai Ti; Su Li; Zebang Xia; Anas Muhammad (Resources Policy, 2024)

Spatio- temporal juvenile corals (Scleractinia) following the 2016 coral bleaching event at the Pieh Islands Marine Tourism Park (PIMTP), West Sumatra Province, Indonesia - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Risandi Dwirama Putra; Ni Wayan Purnama Sari; Rikoh M. Siringoringo; Tri Aryono Hadi; Giyanto; Raden Sutiadi; Ana Faricha; Yuwanda Ilham; et al. (Regional Studies in Marine Science, 2024)

Anatomical and Ionomics Investigation of Bread Wheat (Triticum aestivum L.) to Decipher Tolerance Mechanisms Under Arsenic Stress - Muhammad Anas; Muhammad Saeed; Kashif Naeem; Munib Ahmed Shafique; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2024)

Sustainable solutions: exploring risks and strategies in Pakistan’s seafood trade for marine conservation - Muhammad Mohsin; Hengbin Yin; Ana Mehak (Frontiers in Marine Science, 2024)
Global literature highlights risks in the seafood trade and suggests mitigation methods, but these issues are often overlooked in developing countries, particularly in Pakistan, due to ineffective policy implementation. This underlines the urgent need for a thorough investigation into Pakistan’s seafood trade to address its multifaceted risks and revive this agricultural sector. This study is notable for being the first to explore these uncharted risks in Pakistan’s seafood trade, which can help achieve the sustainable development goals (SDGs) of the United Nations, particularly SDG 14 (life underwater) and SDG 2 (zero hunger). Primary data were gathered from 626 respondents using snowball sampling and structured questionnaires from July 13, 2023, to December 27, 2023. The study used multi-criteria decision analysis, including fuzzy Analytic Hierarchy Process (AHP) and Importance Performance Analysis (IPA), and multivariate analysis, comprising Analysis of Moment Structures (AMOS), to analyze the data. The findings revealed that ‘environmental risks’ were the most significant, followed by ‘infrastructure and logistic risks’. The biggest sub-risk identified for managerial focus includes overfishing. Controlling overfishing is critical for ensuring marine conservation and reviving the seafood trade. Several sub-risks, like seafood prices, marketing strategies, consumer preferences, and tastes, are critical but never addressed in the regulations. Furthermore, risk perception mediates the relationship between risk management and risk performance. The survey respondents reported low-risk perception and inadequate management measures. Besides, this study expounds on ramifications, shortcomings, and areas for further research.

Strengthening education and training programmes for medical physics in Asia and the Pacific: the IAEA non-agreement technical cooperation (TC) regional RAS6088 project - Noriah Jamal; Anchali Krisanachinda; Virginia Tsapaki; Md Rafiqul Islam; Supriyanto Pawiro; Muhammad Al Omari; Chai Hong Yeong; Thinn Thinn Myint; Muhammad Basim Kakakhel; Mohammad Hassan Kharita; Cheow Lei James Lee; Anas Ismail; et al. (Physical and Engineering Sciences in Medicine, 2024)

The dominant influence of terrain and geology on vegetation mortality in response to drought: Exploring resilience and resistance - Linying Xiao; Jinxing Zhou; Xiuqin Wu; Muhammad Anas Khan; Sen Zhao; Xinliang Wu (CATENA, 2024)

Diagenetic controls on the quality of shallow marine sandstones: An example from the Cambro-Ordovician Saq Formation, central Saudi Arabia - Abdulwahab Muhammad Bello; Anas Muhammad Salisu; Abdullah Alqubalee; Abduljamiu O. Amao; Murtada Al-Hashem; Abdulkarim Al-Hussaini; Khalid Al-Ramadan (Journal of African Earth Sciences, 2024)

Soybean yield variability in Northern Ghana: Effects of rhizobia inoculation, P application, and soil exchangeable Mg content - Alfred Balenor Buernor; Muhammad Rabiu Kabiru; Bouchra Chaouni; Edwin K. Akley; Anas Raklami; Francis B. T. Silatsa; Michael Asante; Sara Dahhani; Mohamed Hafidi; Jibrin Mohammed Jibrin; Martin Jemo (Plant and Soil, 2024)

Deep learning and LiDAR integration for surveillance camera-based river water level monitoring in flood applications - Nur Atirah Muhadi; Ahmad Fikri Abdullah; Siti Khairunniza Bejo; Muhammad Razif Mahadi; Ana Mijic; Zoran Vojinovic (Natural Hazards, 2024)

How does green investment, financial inclusion, and digitalization drive environmental sustainability in China? A perspective based on quantile-on-quantile regression and wavelet coherence analysis - Xiaomeng Deng; Satar Bakhsh; Kishwar Ali; Muhammad Anas (Environment, Development and Sustainability, 2024)

Fostering environmental sustainability: An analysis of green investment and digital financial inclusion in China using quantile-on-quantile regression and wavelet coherence approach - Wei Zhang; Satar Bakhsh; Kishwar Ali; Muhammad Anas (Gondwana Research, 2024)

Childhood-related neural genotype–phenotype in ATP1A3 mutations: comprehensive analysis - Osama Y. Muthaffar; Asma Alqarni; Jumana A. Shafei; Sarah Y. Bahowarth; Anas S. Alyazidi; Muhammad Imran Naseer (Genes & Genomics, 2024)

A Comprehensive Review of Hydrogel-Based Drug Delivery Systems: Classification, Properties, Recent Trends, and Applications - Huma Hameed; Saleha Faheem; Ana Cláudia Paiva-Santos; Hafiz Shoaib Sarwar; Muhammad Jamshaid (AAPS PharmSciTech, 2024)

Substation of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2024)

Energy transition and environmental stability prospects for OECD economies: The prominence role of environmental governance, and economic complexity: Does the geopolitical risk matter? - Satar Bakhsh; Wei Zhang; Kishwar Ali; Muhammad Anas (Journal of Environmental Management, 2024)

Comparative morpho-physiological traits, antioxidant defense and nutritional profiling under Cd stress of japonica-indica elite rice (Oryza sativa L.) cultivars - Alvina Hayat; Muhammad Anas; Zeenat Shaheen; Aliza Falak; Umar Masood Quraishi (Journal of Crop Science and Biotechnology, 2024)

Arsenic accumulation pattern in water-soil-rice systems: A study of tolerance mechanisms and associated health risks - Muhammad Saeed; Muhammad Anas; Umar Masood Quraishi; Riffat Naseem Malik (Science of The Total Environment, 2024)

2D Ti3C2Tx-MXene nanosheets and graphene oxide based highly sensitive humidity sensor for wearable and flexible electronics - Waqas Waheed; Shoaib Anwer; Muhammad Umair Khan; Muhammad Sajjad; Anas Alazzam (Chemical Engineering Journal, 2024)

Pathological effects of feeding aflatoxin-contaminated feed on immune status and reproductive performance of juvenile white leghorn males and its mitigation with ∝-tocopherol and Moringa oleifera - Muhammad Kashif Saleemi; Ahmad Raza; Aisha Khatoon; Muhammad Zubair; Shafia Tehseen Gul; Xu Yongping; Bilal Murtaza; Faqir Muhammad; Bushra Akhtar; Farhat Jubeen; Farzana Rizvi; Khawar Zubair; et al. (Environmental Science and Pollution Research, 2023)

Impact of kaolinite and iron oxide cements on resistivity and quality of low resistivity pay sandstones - Anas Muhammad Salisu; Abdullah Alqubalee; Abdulwahab Muhammad Bello; Abdulkarim Al-Hussaini; Abdulrauf R. Adebayo; Abduljamiu O. Amao; Khalid Al-Ramadan (Marine and Petroleum Geology, 2023)

Heavy metals contamination in vegetables irrigated with wastewater: a case study of underdeveloping regions of Pakistan - Ana Aslam; Asifa Naz; Syed Shahid Hussain Shah; Farah Rasheed; Raheela Naz; Amina Kalsom; Nisa Mukhtar; Abid Niaz; Muhammad Aftab; Irfan Rasheed; Muhammad Arfan Ul Haq; Muhammad Arif; et al. (Environmental Geochemistry and Health, 2023)

General equilibrium model-based green finance, decarbonization and high-quality economic development: a new perspective from knowledge networks - Jie Han; Wei Zhang; Cem Işık; Anas Muhammad; Jiale Yan (Environment, Development and Sustainability, 2023)

Green means long life - green competencies for corporate sustainability performance: A moderated mediation model of green organizational culture and top management support - Murad Ali; Mehwish Malik; Muhammad Zafar Yaqub; Charbel Jose Chiappetta Jabbour; Ana Beatriz Lopes de Sousa Jabbour; Hengky Latan (Journal of Cleaner Production, 2023)

Progress in genome-wide identification of RBPs and their role in mitigating stresses, and growth in plants - Muhammad Haroon; Hala Tariq; Rabail Afzal; Muhammad Anas; Shanza Nasar; Neha Kainat; Sajid Fiaz; Uswa Irfan; Fahad Idrees; Muhammad Mubashar Zafar (South African Journal of Botany, 2023)

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Sustainable bioethanol production from first- and second-generation sugar-based feedstocks: Advanced bibliometric analysis - Cláudia Elisa César Guimarães; Francisco Simão Neto; Viviane de Castro Bizerra; Jean Gleison Andrade do Nascimento; Roberta Bussons Rodrigues Valério; Paulo Gonçalves de Sousa Junior; Ana Kátia de Sousa Braz; Rafael Leandro Fernandes Melo; Juliana de França Serpa; Rita Karolinny Chaves de Lima; Artemis Pessoa Guimarães; Maria Cristiane Martins de Souza; et al. (Bioresource Technology Reports, 2023)

Integrating low levels of organic fertilizer improves soil fertility and rice yields in paddy fields by influencing microbial communities without increasing CH4 emissions - Anas Iqbal; Xiangru Tang; Izhar Ali; Pengli Yuan; Rayyan Khan; Zaid Khan; Muhammad Adnan; Shanqing Wei; Ligeng Jiang (Applied Soil Ecology, 2023)

Citrinin as a potential anti-cancer therapy: A comprehensive review - Ag-Anne P.M. de Menezes; Raí P.S. Aguiar; José V.O. Santos; Chandan Sarkar; Muhammad T. Islam; Antonio L. Braga; Mohammad M. Hasan; Felipe C.C. da Silva; Javad Sharifi-Rad; Abhijit Dey; Daniela Calina; Ana A.C. Melo-Cavalcante; et al. (Chemico-Biological Interactions, 2023)

The construction of green finance and high-quality economic development under China’s SDGs target - Jie Han; Qinglan Zheng; Danxi Xie; Anas Muhammad; Cem Isik (Environmental Science and Pollution Research, 2023)

Anticancer effects of phytol against Sarcoma (S-180) and Human Leukemic (HL-60) cancer cells - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Ana Maria Oliveira Ferreira da Mata; Antonielly Campinho dos Reis; Rosália Maria Torres de Lima; José Roberto de Oliveira Ferreira; João Marcelo de Castro e Sousa; Paulo Michel Pinheiro Ferreira; Ana Amélia de Carvalho Melo-Cavalcante; Abdur Rauf; Hassan A. Hemeg; Khalaf F. Alsharif; et al. (Environmental Science and Pollution Research, 2023)

Islamic corporate sustainability practices index aligned with SDGs towards better financial performance: Evidence from the Malaysian and Indonesian Islamic banking industry - Amin Jan; Haseeb Ur Rahman; Muhammad Zahid; Anas A. Salameh; Parvez Alam Khan; Mamdouh Abdulaziz Saleh Al-Faryan; Roslizawati Binti Che Aziz; H. Elhosiny Ali (Journal of Cleaner Production, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

Numerical investigation of thermal-hydraulic design of a printed circuit steam generator - Muhammad Ali Khan; Syed Anas Sohail; Khalid Waheed; Waseem Siddique; Muhammad Ilyas; Fatih Aydogan; Kamran Rasheed Qureshi; Imran Shaban Bhatti (Annals of Nuclear Energy, 2023)

Carbon and nitrogen stable isotope compositions provide new insights into the phenotypic plasticity of the invasive species Carpobrotus sp. pl. in different coastal habitats - Marta Pérez-Diz; Berea Rodríguez-Addesso; Muhammad Iftikhar Hussain; Jonatan Rodríguez; Ana Novoa; Luís González (Science of The Total Environment, 2023)

Assessment of knowledge, perception, practices and drivers of antimicrobial resistance and antimicrobial usage among veterinarians in Pakistan - Ayesha Saman; Mamoona Chaudhry; Muhammad Ijaz; Waseem Shaukat; Muhammad Usman Zaheer; Ana Mateus; Abdul Rehman (Preventive Veterinary Medicine, 2023)

Oxidative stress mediated cytogenotoxicological effects of phytol in wistar albino rats - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Antonielly Campinho dos Reis; José Victor de Oliveira Santos; Adriana Maria Viana Nunes; Felipe Cavalcante Carneiro da Silva; Keylla da Conceição Machado; João Marcelo de Castro e Sousa; Željko Reiner; Miquel Martorell; Sharmila Fagoonee; Javad Sharifi-Rad; et al. (Advances in Traditional Medicine, 2023)

Environmental performance measurement in arts and cultural organisations: Exploring factors influencing organisational changes - Ana Rita Domingues; Muhammad Usman Mazhar; Richard Bull (Journal of Environmental Management, 2023)

Cleaner production of biodiesel from novel non-edible seed oil (Carthamus lanatus L.) via highly reactive and recyclable green nano CoWO3@rGO composite in context of green energy adaptation - Mamoona Munir; Muhammad Saeed; Mushtaq Ahmad; Amir Waseem; Mustafa Alsaady; Saira Asif; Anas Ahmed; Mohd Shariq Khan; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; Pau Loke Show (Fuel, 2023)

Biochar in Combination with Nitrogen Fertilizer is a Technique: To Enhance Physiological and Morphological Traits of Rice (Oryza sativa L.) by Improving Soil Physio-biochemical Properties - Izhar Ali; Quan Zhao; Ke Wu; Saif Ullah; Anas Iqbal; He Liang; Jing Zhang; Ihsan Muhammad; Amanullah; Abdullah Khan; Asad Ali Khan; Ligeng Jiang (Journal of Plant Growth Regulation, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Characterization of Exotic, Native and Wild-Type Genotypes of Sugarcane (Saccharum spp. Hybrids) for Internal Nitrogen Use Efficiency Under Different Nitrogen Levels - Muhammad Anas; Krishan K. Verma; Ikram Ul Haq; Muhammad Naeem; Qiang Li; Fen Liao; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Development of a reversible regulatory system for gene expression in the cyanobacterium Synechocystis sp. PCC 6803 by quorum-sensing machinery from marine bacteria - Muhammad Junaid; Yu Inaba; Ana Otero; Iwane Suzuki (Journal of Applied Phycology, 2021)

A feasibility study on microwave imaging of bone for osteoporosis monitoring - Bilal Amin; Atif Shahzad; Lorenzo Crocco; Mengchu Wang; Martin O’Halloran; Ana González-Suárez; Muhammad Adnan Elahi (Medical & Biological Engineering & Computing, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Cytogenotoxicological Effects of the Methanolic Extract of Dysophylla auricularia - Muhammad Torequl Islam; Eunus S. Ali; Shaikh Jamal Uddin; Swati Tripathi; Ana Amélia de Carvalho Melo-Cavalcante; Siddhartha Kumar Mishra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Ecological structure and carbon storage in traditional silvopastoral systems in Nicaragua - Aura Cárdenas; Ana Moliner; Chiquinquirá Hontoria; Muhammad Ibrahim (Agroforestry Systems, 2019)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Occupational and life-style factors-acquired mutagenicity in agric-workers of northeastern Brazil - Tatiana Vieira Souza Chaves; Muhammad Torequl Islam; Manoel Odoríco de Moraes; Marcus Vinícius Oliveira Barros de Alencar; Débora Cássia Vieira Gomes; Rodrigo Mendes de Carvalho; Sharbel Weider Maluf; Fabrício Pires de Moura do Amaral; Márcia Fernanda Correia Jardim Paz; Gilberto Santos Cerqueira; Hercília Maria Lins Rolim; João Marcelo de Castro e Sousa; et al. (Environmental Science and Pollution Research, 2017)

Cytotoxicity and genotoxicity of Guaribas river water (Piauí, Brazil), influenced by anthropogenic action - João Marcelo de Castro e Sousa; Ana Paula Peron; Louridânya da Silva e Sousa; Mércia de Moura Holanda; Ataíde de Macedo Vieira Lima; Vitor Alves de Oliveira; Felipe Cavalcanti Carneiro da Silva; Leonardo Henrique Guedes de Morais Lima; Leomá Albuquerque Matos; Sandra Maria Mendes de Moura Dantas; Raí Pablo Sousa de Aguiar; Muhammad Torequl Islam; et al. (Environmental Monitoring and Assessment, 2017)